2015
DOI: 10.1136/annrheumdis-2015-eular.2075
|View full text |Cite
|
Sign up to set email alerts
|

OP0284 Long Noncoding RNA MIR503HG is a Novel Factor in the Pathogenesis of Systemic Sclerosis

Abstract: BackgroundLong noncoding RNAs (LncRNAs) are a novel class of noncoding transcripts with diverse regulatory functions, e.g. imprinting regulation, dosage compensation, cell cycle regulation, pluripotency and retrotransposon silencing. Dysregulation of lncRNAs is increasingly recognized to contribute to the disease pathogenesis, such as cancer, autoimmune disorders and neurodegeneration.ObjectivesTo identify candidate lncRNAs in systemic sclerosis (SSc) and investigate their function, in particular in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A study by Muys et al (40) showed that the lncRNA MIR503HG impairs the migration and invasion capacities in a choriocarcinoma tumor cell, indicating a potential role in human reproduction and tumorigenesis. Knockdown of MIR503HG leads to a strong downregulation of the target gene collagen type 1 α1 chain, indicating an important role of MIR503HG in diseases, including systemic sclerosis (41). As the lncRNAs target genes, mRNA expression is commonly involved in the pathogenesis and prognosis of lung cancer (42).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Muys et al (40) showed that the lncRNA MIR503HG impairs the migration and invasion capacities in a choriocarcinoma tumor cell, indicating a potential role in human reproduction and tumorigenesis. Knockdown of MIR503HG leads to a strong downregulation of the target gene collagen type 1 α1 chain, indicating an important role of MIR503HG in diseases, including systemic sclerosis (41). As the lncRNAs target genes, mRNA expression is commonly involved in the pathogenesis and prognosis of lung cancer (42).…”
Section: Discussionmentioning
confidence: 99%
“…In a global microarray analysis of tissues from patients with systemic sclerosis (SSc), MIR503HG was identified as significantly up-regulated in fibrotic tissues from the skin, liver and lungs of Ssc patients. MIR503HG could be induced within 6 hours of treatment with TGF-in vitro, and induction of MIR503HG by TGF-was impaired by depletion of SMAD3, demonstrating importance of the TGF-pathway in MIR503 expression 8 . Depletion of MIR503HG in skin fibroblasts resulted in decreased expression of COLA1A1, fibronectin, and aSMA, suggesting MIR503HG might function as a regulator of the myofibroblast phenotype 8 .…”
Section: Discussionmentioning
confidence: 95%
“…MIR503HG could be induced within 6 hours of treatment with TGF-in vitro, and induction of MIR503HG by TGF-was impaired by depletion of SMAD3, demonstrating importance of the TGF-pathway in MIR503 expression 8 . Depletion of MIR503HG in skin fibroblasts resulted in decreased expression of COLA1A1, fibronectin, and aSMA, suggesting MIR503HG might function as a regulator of the myofibroblast phenotype 8 .…”
Section: Discussionmentioning
confidence: 95%
“…The MIR503HG inhibitors SD208 and SB31532 can significantly reduce the expression of type I collagen, fibronectin and α-smooth actin. MIR503HG may play an important role in the development of myofibroblasts in the context of SSc [110].…”
Section: Lncrnas In Rheumatic Diseasesmentioning
confidence: 99%